Actuarial executives and insurer’s risk level : do actuarial executives make difference? - Ang, Zie Sen (2013)
We examine the relationship between the presence of actuarial and other risk-related top executives on the risk levels of property-casualty insurance companies in the United States during 2007-2010. We find that the presence of actuarial top executives is associated with lower cash ratio, higher reinsurance assumed and higher reinsurance ceded in an insurance company, and do not observe similar results for chief risk officers (CRO) and other risk-related positions. We also identify features that insurance firms tend to exhibit associated with the change of actuarial professionals in top executives’ positions.